(untitled) (Asian Journal of Medical and Biological Research, 2022)
Salinity is a serious problem affecting one third of the irrigation land and limiting the yield potential of modern rice (Oryza sativa L.) varieties. To increase our understanding of salt tolerance mechanisms in rice for better production, knowledge of salinity effects on rice seedling growth and yield components is inevitable. Despite of large number of studies on salinity tolerance of rice, we have very limited knowledge on the overall effect of salinity on rice seedlings growth. The experiment was carried out to assess the responses of salinity on the growth, nutrient accumulation and yield of rice genotypes BRRI dhan29 (salt-sensitive) and BINA dhan-10 (salt-tolerant). The pot experiment was conveyed at the net house to evaluate the response of two rice genotypes at five levels of salt stresses (0, 25, 50, 75, 100 mM NaCl) at the vegetative stage. After harvesting of rice, electrical conductivity of soil was analyzed. Growth, yield components, grain and straw yields were evaluated. Binadhan-10 showed a higher salt tolerance in physiological parameters of rice than BRRI dhan29. A significant reduction of growth, yield components, grain and straw yields of both rice genotypes was found in response to salt stress. At different salt stress conditions nutrient uptake (NPS) and K+/Na+ ratio was significantly decreased in both rice genotypes. Yet, K+/Na+ ratio was more in salt-tolerant variety than salt-sensitive variety. Asian J. Med. Biol. Res. 2022, 8 (4), 230-239